2003
DOI: 10.1088/0953-2048/17/1/014
|View full text |Cite
|
Sign up to set email alerts
|

Alternating current loss in rectangular superconducting bars with a constant critical-current density

Abstract: When an alternating current of amplitude I m is applied to a hard superconducting rectangular (2a × 2b) bar of critical current I c , the loss per cycle per unit length Q is calculated from Bean's critical-state model. The resultant normalized loss 2πQ/µ 0 I 2 c for a wide range of current amplitudes and bar's aspect ratio is expressed by numerical curves, approximate analytical formulae and a practical table.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…for the single Roebel cable, where Q is the loss per cycle and cable length, shows that for low current amplitudes it is proportional I m (or Q I m 4 µ ), figure 8. This kind of dependence, typical for thin strips, appears always when the dominant ac loss contribution is from the flux penetration from the narrow edges of the tapes [35]. With increasing the current amplitude, the behaviour of the Roebel cable approaches to a mono-block, with a loss per cycle proportional to I m 3 .…”
Section: Stand-alone Roebel-cable Solenoid: Modellingmentioning
confidence: 92%
See 1 more Smart Citation
“…for the single Roebel cable, where Q is the loss per cycle and cable length, shows that for low current amplitudes it is proportional I m (or Q I m 4 µ ), figure 8. This kind of dependence, typical for thin strips, appears always when the dominant ac loss contribution is from the flux penetration from the narrow edges of the tapes [35]. With increasing the current amplitude, the behaviour of the Roebel cable approaches to a mono-block, with a loss per cycle proportional to I m 3 .…”
Section: Stand-alone Roebel-cable Solenoid: Modellingmentioning
confidence: 92%
“…from the narrow edges of the tapes [35]. With increasing the current amplitude, the behaviour of the Roebel cable approaches to a mono-block, with a loss per cycle proportional to I 3 m .…”
Section: Hv LVmentioning
confidence: 98%
“…1 for properties) with the numerical results obtained with FEMPAR. The problem of a HTS tape magnetized by a current flowing through it has been solved by several authors (see, e.g., [55,56,57]). Besides, several comparisons between experimental and numerical results can be found, e.g., in [58,59,60].…”
Section: 3mentioning
confidence: 99%
“…When the aspect ratio is changing, the slope of the first cosine components is varying [2]. Interestingly, in the three cases compared here, the higher sine components are practically identical.…”
Section: Fig 1 Experimental Setupmentioning
confidence: 67%
“…This can be performed only with the help of numerical methods. In our case, the minimization of magnetic energy variation was used [2], which is equivalent to the critical state model [3]. Indeed, we have found that the numerical results lie in the area limited by two analytical models mentioned above, when studying the Q(F ) dependence, where F is the ratio of AC current amplitude, I a , with respect to the wire's critical current, I c .…”
Section: Introductionmentioning
confidence: 99%